49.3k views
4 votes
Help pleaseeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeee

Help pleaseeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeee-example-1

2 Answers

1 vote

Answer: 1328

Explanation:

4*7^3 - 7*7 + 5 = 1328

User Sanan Ali
by
4.9k points
3 votes

Answer:

f(x) = 4x³ - 7x + 5

f(x) = 4x³ - 7x + 5(a). f(0) = 5

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Check

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,using the formula above

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,using the formula abovef(0) = 4(0)³ - 7(0) + 5

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,using the formula abovef(0) = 4(0)³ - 7(0) + 5 = 0 - 0 + 5

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,using the formula abovef(0) = 4(0)³ - 7(0) + 5 = 0 - 0 + 5 = 5.

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,using the formula abovef(0) = 4(0)³ - 7(0) + 5 = 0 - 0 + 5 = 5. ✓(b). f(7) =

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,using the formula abovef(0) = 4(0)³ - 7(0) + 5 = 0 - 0 + 5 = 5. ✓(b). f(7) = Using the formula above,

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,using the formula abovef(0) = 4(0)³ - 7(0) + 5 = 0 - 0 + 5 = 5. ✓(b). f(7) = Using the formula above, f(7) = 4(7)³ - 7(7) + 5

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,using the formula abovef(0) = 4(0)³ - 7(0) + 5 = 0 - 0 + 5 = 5. ✓(b). f(7) = Using the formula above, f(7) = 4(7)³ - 7(7) + 5 = 4(343) - 49 + 5

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,using the formula abovef(0) = 4(0)³ - 7(0) + 5 = 0 - 0 + 5 = 5. ✓(b). f(7) = Using the formula above, f(7) = 4(7)³ - 7(7) + 5 = 4(343) - 49 + 5 =1372 - 54

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,using the formula abovef(0) = 4(0)³ - 7(0) + 5 = 0 - 0 + 5 = 5. ✓(b). f(7) = Using the formula above, f(7) = 4(7)³ - 7(7) + 5 = 4(343) - 49 + 5 =1372 - 54 = 1318

f(x) = 4x³ - 7x + 5(a). f(0) = 5 Checkif x=0,using the formula abovef(0) = 4(0)³ - 7(0) + 5 = 0 - 0 + 5 = 5. ✓(b). f(7) = Using the formula above, f(7) = 4(7)³ - 7(7) + 5 = 4(343) - 49 + 5 =1372 - 54 = 1318

(c). f(-5) =

Using the formula above

f(-5) = 4(-5)³ - 7(-5) + 5

= 4(-125) + 35 + 5

= -500 + 40

= -460

*remember to use a calculator to check the answers

Hope this helps xoxo....

User Pauly
by
5.5k points